A Case Study on the Translation Procedures of Puns in Advertisements from Chinese to Malay: (Kajian Kes Prosedur Penterjemahan Mainan Kata Teks Iklan daripada Bahasa Cina kepada Bahasa Melayu) (Jurnal Bahasa, 2019)
This paper discusses the translation of puns in advertisements fromChinese to Malay based on the pun translation methods introduced by Delabastita (1996). The objective of the study is to identify the translation procedures that can be applied in translating puns in advertisements from Chinese into Malay. Four advertisements with puns were selected as the source texts for this study. This study is based on several approaches: i) rhetoric in advertising, ii) translation of meaning and iii) translation procedures of puns by Delabatita. The discussion is also guided by three research questions. Those questions are, what are rhetoric elements found it the context of advertsement understudy?, how are the wordplays translated in the advertisements, and what are the procedures used to translate the Chinese advertisements into Malay? The findings show that three translation procedures proposed by Delabastita (1996), namely 'puns in the source text are translated as puns in the target text', 'puns translated as non-puns' and 'puns are translated as related to rhetorical devices' are the translation procedures that can be adopted in the translation of puns from Chinese to Malay. Omission and adaptation, however, are among two necessary procedures adopted to omit taboo images and to replace the meanings of taboo symbols.Keywords: translation of puns, advertisements, taboo, translation procedures